2016
DOI: 10.1590/1807-3107bor-2016.vol30.0040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different torque levels on the implant-abutment interface in a conical internal connection

Abstract: The fit of the implant-abutment interface was assessed by the metallographic technique and by scanning electron microscopy (SEM), using solid abutment types at different torque levels. Forty Morse taper connections and forty solid abutments were used at different torque levels (repeated after 10 minutes) in the following groups (n = 10): 25 Ncm (group g1), 30 Ncm (group g2), 35 Ncm (group g3), and 40 Ncm (group g4). The samples were embedded in a metallographic resin, sectioned lengthwise, and polished. SEM im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 16 publications
2
24
1
5
Order By: Relevance
“…The implants used in this study, in fact, present a conical connection (10°) combined with an internal hexagon, characterized by high mechanical stability [28–30]. The conical implant-abutment connections can guarantee high stability, as demonstrated by several recent works [3234]. In addition, these implants possess an integrated platform switching [29, 30]; this is useful to maintain and preserve the tissue volumes, as previously reported [3537]; accordingly, a minimal bone resorption was found around the implants, with a mean overall peri-implant marginal bone loss of 0.40 mm (±0.20) 4 months after the implant placement; this bone loss increased to 0.43 mm (±0.15) at the 1-year follow-up control.…”
Section: Discussionmentioning
confidence: 98%
“…The implants used in this study, in fact, present a conical connection (10°) combined with an internal hexagon, characterized by high mechanical stability [28–30]. The conical implant-abutment connections can guarantee high stability, as demonstrated by several recent works [3234]. In addition, these implants possess an integrated platform switching [29, 30]; this is useful to maintain and preserve the tissue volumes, as previously reported [3537]; accordingly, a minimal bone resorption was found around the implants, with a mean overall peri-implant marginal bone loss of 0.40 mm (±0.20) 4 months after the implant placement; this bone loss increased to 0.43 mm (±0.15) at the 1-year follow-up control.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we can say that the conical implant connection system is more favorable insofar as the maintenance of the marginal bone is concerned [7,22,[26][27][28][29][30][31].…”
Section: Conicalmentioning
confidence: 99%
“…11,30 Thus, several studies have been done to determine the association between insertion torque and bone related changes and have concluded a positive correlation between the two. [10][11][12][13][14][15][16][17][18][19][20] The relation between insertion torque, osseointegration and implant success-an evidence based overview: Successful osseointegration is an outcome of good quality of primary stability which in turn depends on insertion torque. [31][32][33] Osseointegration is a structural and functional association between living bone and the loading implant interface, is crucial for implant stability, and is well thought-out a requirement for implant loading and clinical success of end osseous dental implants in long run.…”
Section: What Are the Key Factors Affecting Insertion Torque?mentioning
confidence: 99%
“…Few studies have indicated insertion torque near the range of 35 Ncm to be satisfactory while some found no bone damage up to 176 Ncm. 3,10,16,17 However, impact of high and low insertion torque depends on various parameters. 18 In this review article we will discuss the effect of high insertion torque and bone related changes which ultimately decide the success and failure of an implant.…”
Section: Introductionmentioning
confidence: 99%